Improvement of Coal Handling System to Minimize Dust During Operation at PLTU IPP Kendari-3 - Ilham, Nur (Jurnal Locus Penelitian dan Pengabdian, 2026)
The coal handling process in coal-fired power plants (CFPPs) is a major source of dust emissions, which can adversely affect environmental quality, occupational health, and mechanical equipment reliability. Therefore, systematic efforts to improve this process are essential to ensure safe, efficient, and environmentally responsible operations. At PLTU IPP Kendari-3, PT DSSP Power Kendari implemented a comprehensive coal handling system enhancement program from 2019 to 2025 as part of its emission management strategy. These initiatives included installing fog cannons in the coal shed, applying water spray systems in the coal yard and along conveyor lines, replacing primary belt cleaners, and installing secondary belt cleaners to minimize residual coal buildup. Additional measures encompassed routine maintenance of the dedusting system, installing bunker covers on belt conveyor #3, adding rolling doors in the fly ash unloading area, and modifying the jetty conveyor drop point to reduce particle dispersion. Collectively, these improvements have significantly reduced dust emissions, enhanced occupational safety and health, extended equipment service life, and ensured compliance with environmental regulations and standards. This initiative demonstrates the company’s commitment to sustainable power plant operations and continuous improvement in environmental performance